Korelasi Kedalaman terhadap Nilai Resistivitas dan Parameter Geoteknik (N-SPT dan Kohesi) pada Tanah Vulkanik dengan Analisis Regresi dan Klaster - Ismiralda, Dinta Anindy; Pamungkas, Helmi Setia Ritma; Irianto, Singgih (Jurnal Sains dan Teknologi (JSIT), 2025)
This study aims to analyze the relationship between depth, resistivity, and geotechnical parameters (SPT-N and cohesion) of volcanic soils on the Cisadane River slopes, South Bogor, using regression and cluster analysis. Methods included geoelectrical surveys with Schlumberger and Wenner–Schlumberger configurations, borehole drilling up to 26.5 m with SPT tests, and direct shear laboratory testing for cohesion values. Regression analysis indicated a significant positive relationship between depth and SPT-N (R² = 0.411; p < 0.05), while cohesion showed a positive but statistically insignificant trend, and resistivity exhibited a weak negative relationship with depth. Cluster analysis grouped the data into three categories: (1) shallow upper layer with high resistivity and low SPT values; (2) dominant middle layer consisting of saturated clayey soils with moderate parameters; and (3) dense to hard lower layer with high resistivity, high SPT values, and stronger cohesion. These results demonstrate that the integration of regression and cluster analysis effectively reveals the relationship between resistivity and the mechanical properties of volcanic soils, thus supporting geotechnical investigations and landslide hazard mitigation in the South Bogor area.